ANDEA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The African Network for the Development of Ecological Agriculture (ANDEA) has now got a base in Ghana. The main aims of this network are to encourage research in biological agriculture and to disseminate the results to farmers. ANDEA encourages the...